2022
DOI: 10.1155/2022/1731701
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Curcumin against Oxygen-Glucose Deprivation/Reoxygenation-Induced Injury in Cultured Primary Rat Astrocyte by Improving Mitochondrial Function and Regulating the ERK Signaling Pathway

Abstract: Objectives. Curcumin (Cur) is a natural polyphenol isolated from turmeric and has potent anti-inflammatory and antioxidant activities. This study aimed to explore the effects and possible mechanisms of curcumin on oxygen-glucose deprivation/reoxygenation (OGD/R)-induced injury in cultured rat astrocyte primary cells. Methods. After screening for effective doses, the cultured rat astrocyte primary cells were divided into three groups: control, OGD/R, and OGD/R + curcumin (10 μM, 20 μM, and 40 μM). Cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It has been reported that many signaling pathways are involved in modulating mitochondrial function, including the Akt/mTOR/nuclear factor kappa B (NF-κB) signaling pathway [40], the PI3K/Akt/mTOR signaling pathway [41], and the extracellular signal-regulated kinase (ERK) signaling pathway [42]. Zhao et al reported that inhibition of mTOR exerted synergistic effects on inhibiting α-SMA expression and cell proliferation [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that many signaling pathways are involved in modulating mitochondrial function, including the Akt/mTOR/nuclear factor kappa B (NF-κB) signaling pathway [40], the PI3K/Akt/mTOR signaling pathway [41], and the extracellular signal-regulated kinase (ERK) signaling pathway [42]. Zhao et al reported that inhibition of mTOR exerted synergistic effects on inhibiting α-SMA expression and cell proliferation [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of curcumin via effects on mitochondrial functions are well-documented. Curcumin demonstrated protective activities against oxygen–glucose deprivation/reoxygenation-induced injury in astrocyte primary cells in vitro through the elevated mitochondrial function and triggering the ERK signaling pathway [ 108 ]. In another study, curcumin demonstrated neuroprotective activities against amyloid-β-induced mitochondrial dysfunction which were associated with the inhibition of the GSK-3β signaling pathway [ 109 ].…”
Section: Senotherapeuticsmentioning
confidence: 99%